Experimental investigation of thermal performance of a double-flow solar air heater having aluminium cans - Ozgen, Filiz; Esen, Mehmet; Esen, Hikmet (Pergamon-Elsevier Science Ltd, 2009)
This study experimentally investigates a device for inserting an absorbing plate made of aluminium cans into the double-pass channel in a flat-plate solar air heater (SAH). This method substantially improves the collector efficiency by increasing the fluid velocity and enhancing the heat-transfer coefficient between the absorber plate and air. These types of collectors had been designed as a proposal to use aluminium materials to build absorber plates of SAHs at a suitable cost. The collector had been covered with a 4-mm single glass plate, in order to reduce convective loses to the atmosphere. Three different absorber plates had been designed and tested for experimental study. In the first type (Type 1), cans had been staggered as zigzag on absorber plate, while in Type 11 they were arranged in order. Type III is a flat plate (without cans). Experiments had been performed for air mass flow rates of 0.03 kg/s and 0.05 kg/s. The highest efficiency had been obtained for Type I at 0.05 kg/s. Also, comparison between the thermal efficiency of the SAH tested in this study with the ones reported in the literature had been presented, and a good agreement had been found. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Solar air heaters; Aluminium cans; Thermal efficiency; Experimental; Double-pass flow